Pengaruh Insentif, Motivasi Kerja, dan Beban Kerja Terhadap Kinerja Karyawan Aviation Security PT. Angkasa Pura I di Bandar Udara Internasional Jenderal Ahmad Yani Semarang - Mohammad Alifian Akbar; You She Melly Anne Dharasta (Student Research Journal, 2023)
The development of air transportation, the airport as an aviation service provider company must balance with quality human resources, especially in the quality of employee performance. The quality of performance of an employee depends on the duties and responsibilities imposed on him. In addition, employee performance also depends on incentives, motivation and workload obtained. This study aims to determine the effect of incentives, motivation and workload partially and simultaneously on the performance of Aviation Security Employees of Pt. Angkasa Pura I at General Ahmad Yani International Airport Semarang. This study used quantitative research methods using questionnaire data collection techniques through Likert scale. And the sample taken in this study amounted to 63 respondents from Aviation Security Employees of Pt. Angkasa Pura I at General Ahmad Yani International Airport Semarang. The results showed that partially the three variables of incentives, and workload on employee performance got positive and significant results, while the motivation variable on employee performance got results that did not have a positive and significant effect. Simultaneously, this study obtained equally positive and significant results with the value of the calculated value of the fcalculate > ftable, which is 119.61 > 2.761, and for the coefficient of determination obtained the result of the rsquare value of 85.9%.